Pengaruh Sarana Prasarana Pembelajaran dan Motivasi Mengajar terhadap Efektivitas Kinerja Guru Sekolah Menengah Atas - Nurdin Nurdin; Hery Purwosusanto; Supriatin Supriatin; Ila Nafilah; Ajeng Tirta Mulyana (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to examine the influence of learning facilities and infrastructure as well as teaching motivation on teacher performance effectiveness. The research employed a survey method. The participants consisted of 80 respondents who were randomly selected from SMA Negeri 7 Tambun, Bekasi. Data were collected using a questionnaire based on a Likert scale. The validity and reliability tests confirmed that the research instrument was valid and reliable, while the normality test indicated that all data were normally distributed. The findings reveal that learning facilities and infrastructure have a significant effect on teacher performance effectiveness. Likewise, teaching motivation has a significant effect on teacher performance effectiveness. The coefficient of determination (R²) indicates that learning facilities and infrastructure, together with teaching motivation, have a strong relationship in explaining teacher performance effectiveness. These findings suggest that improving educational facilities and fostering teachers’ motivation can contribute to enhancing the effectiveness of teacher performance in the learning process.